Genetic variants in m5C modification core genes are associated with the risk of Chinese pediatric acute lymphoblastic leukemia: A five-center case–control study - Wang, Xueliang; Deng, Decheng; Yan, Yaping; Cai, Mansi; Liu, Xiaodan; Luo, Ailing; Liu, Shanshan; Zhang, Xiaohong; Jiang, Hua; Liu, Xiaoping (Frontiers in Oncology, 2023)
Objective To explore the functions of the polymorphisms in 5-methylcytosine (m5C) modification-related coding genes on the susceptibility of pediatric acute lymphoblastic leukemia (ALL). Methods Case–control study and multinomial logistic regression analysis were performed to construct models to evaluate the susceptibility of pediatric ALL. The relationship between five functional SNPs in m5C modification-coding genes and pediatric ALL risk was analyzed. Genotyping of 808 cases and 1,340 healthy samples from South China was identified using a TaqMan assay; odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to estimate the relationship between the five selected SNPs and pediatric ALL susceptibility. Results Among the five analyzed SNPs, NOL1 rs3764909 and NSUN4 rs10252 variants significantly increased the susceptibility of pediatric ALL, while NSUN3 rs7653521, NSUN5 rs1880948, and NSUN6 rs3740102 variants were not associated with the risk of ALL. Stratification analyses demonstrated that NOL1 rs3764909 C>A exhibited a significant association with increased pediatric ALL risk in subgroups of common B ALL, pre-B ALL, T-cell ALL, low and middle risk, other gene fusion types, non-gene fusion, hypodiploid, normal diploid, primitive lymphocytes in marrow < 5% on week 12, and minimal residual disease (MRD) <0.01% on week 12 after induced therapy; NSUN4 rs10252 G>A was related to increased risk of ALL children in subgroups of age ≥ 120 months, normal white blood cell (WBC) number, middle risk, non-gene fusion, MRD ≥ 0.01 on days 15–19, and primitive lymphocytes in marrow < 5% on day 33 after induced therapy. Compared with the reference haplotype CAGTA, children who harbored haplotypes CCGTG and ACATA were remarkably related to increased ALL susceptibility. rs3764909 and rs10252 varieties of alleles were not associated with MRD levels after the selected chemotherapeutics. Conclusions In conclusion, NOL1 rs3764909 and NSUN4 rs10252 variants were enhanced by pediatric ALL risk and were suggested to be potential biomarkers for pediatric ALL.